Comprehensive numerical modeling and analysis of a cell-based indirect internal reforming tubular SOFC - Nishino, T; Iwai, H; Suzuki, K (2006)
A comprehensive numerical model of an indirect internal reforming tubular Solid Oxide Fuel Cell (IIR-T-SOFC) has been developed. Two-dimensional axisymmetry of the velocity, temperature, and mass transfer fields was assumed in the model, but accommodating the peripheral nonuniformity of electric potential and electric current fields in the tubular cell for the case with internal reforming and electrochemical reactions. By using the developed model, it was examined how the thermal field and power generation characteristics of the cell are affected by gas inlet conditions and filling pattern of the reforming catalyst inside the fuel feed tube. In particular, optimization of the catalyst distribution pattern was demonstrated to be effective in the reduction of the maximum temperature and temperature gradient, in the mitigation of the possible appearance of a hot spot and therefore in making the life of a fuel cell longer with little loss of the power generation performance of the cell. Copyright © 2006 by ASME.